2023
DOI: 10.3389/fpubh.2023.1106732
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood cadmium with all-cause and cause-specific mortality in patients with hypertension

Abstract: BackgroundCadmium is a commonly found heavy metal with a prolonged biological half-life, which results in long-term health burden for the population. Prior studies have demonstrated an association between blood cadmium and hypertension. However, few studies examined the relationship between blood cadmium and long-term health outcomes in patients with hypertension. This study aimed to investigate the association of blood cadmium with mortality in patients with hypertension.MethodsThis study analyzed data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Epidemiological studies implicating Cd exposure as a significant contributor to total global mortality and morbidity can be found in Table 4. In the U.S. hypertension cohort [127], blood Cd levels ≥ 0.80 µg/L were associated with 1.85-, 1.76-, and 3.41-fold increases in the mortality from any causes, CVD, and Alzheimer's disease, respectively. Cd appeared to increase CVD mortality markedly (OR 2.12) among non-smokers who had hypertension [127].…”
Section: Cadmium and The World's Leading Causes Of Deathmentioning
confidence: 98%
See 2 more Smart Citations
“…Epidemiological studies implicating Cd exposure as a significant contributor to total global mortality and morbidity can be found in Table 4. In the U.S. hypertension cohort [127], blood Cd levels ≥ 0.80 µg/L were associated with 1.85-, 1.76-, and 3.41-fold increases in the mortality from any causes, CVD, and Alzheimer's disease, respectively. Cd appeared to increase CVD mortality markedly (OR 2.12) among non-smokers who had hypertension [127].…”
Section: Cadmium and The World's Leading Causes Of Deathmentioning
confidence: 98%
“…In the U.S. hypertension cohort [ 127 ], blood Cd levels ≥ 0.80 μg/L were associated with 1.85-, 1.76-, and 3.41-fold increases in the mortality from any causes, CVD, and Alzheimer’s disease, respectively. Cd appeared to increase CVD mortality markedly (OR 2.12) among non-smokers who had hypertension [ 127 ].…”
Section: Global Health Threat Of Environmental Cadmiummentioning
confidence: 99%
See 1 more Smart Citation
“…Some epidemiological studies have shown that long-term, even low levels of cadmium exposure are closely associated with neurological diseases, including multiple sclerosis [9], ischemic stroke [10], and cognitive decline [11][12][13][14]. Additionally, higher cadmium exposure is associated with increased risk of Alzheimer's disease mortality [15][16][17]. However, several studies show there is no relationship between cadmium exposure and cognitive function [18][19][20].…”
Section: Introductionmentioning
confidence: 99%